Planning for green infrastructure using multiple urban ecosystem service models and multicriteria analysis - Lourdes, Karen T.; Hamel, Perrine; Gibbins, Chris N.; Sanusi, Ruzana; Azhar, Badrul; Lechner, Alex M. (Elsevier, 2022)
Unprecedented urban growth and extensive land use change especially in the Global South has placed increasing pressure on urban ecosystem services (UES). While there are numerous studies modelling and mapping ecosystem services, integrating the outputs of multiple ecosystem service assessments to provide recommendations for nature-based planning remains a challenge. The objective of this study is to characterise the spatial distribution of multiple UES in a rapidly urbanising catchment and to develop a systematic approach to facilitate the integration of UES into planning green infrastructure (GI). We used InVEST models to spatially quantify and map six realised UES (heat mitigation, runoff retention, sediment retention, scenic quality, urban recreation and agricultural production (i.e., ‘urban farming’)) in a rapidly developing, peri-urban catchment in Greater Kuala Lumpur, Malaysia. We identified synergies and tradeoffs between services and assessed the cooccurrence and overlap of hotspots between multiples services. Our assessment revealed that densely built areas generally had low UES provision. In the final step, we conducted a multicriteria analysis using ecosystem services-based criteria to identify locations for five GI strategies: conservation of headwaters, reforestation for biodiversity, development and conservation of urban parks and greening of built infrastructure (e.g., green walls and roofs). The selection of the appropriate GI strategy must consider the degree of urban development, especially in areas where multiple strategies were suitable. The findings of our study support GI planning within the catchment and the methods applied can be adapted to support sustainable land use management in urban areas globally.